Evaluation on Bedah Kampung Program - Achmadi Jayaputra (Jurnal Penelitian Kesejahteraan Sosial, 2014)
Bedah Kampung Program is an integrated poverty reduction efforts including behaviour change, improvement of social relations, meeting the needs of the home and the environment, as well as increasing economic status of the poor.The research question is how the policy of the Ministry of Social Affairs in Bedah Kampung Program goes? The research goal is to understand and describe Bedah Kampung Program Policy and factors that affect the implementation. The method used in this research is comparative analysis of social reality betwen empiric conditions with ideal as guidelined by BedahKampung Program in 2012. Sources of data obtained from stakeholders or the implementors of the Ministry of Social AffairsProgram, local social agents, elements of such a companion, community leaders, and beneficiaries. Research sites in Pandeglang (Banten) and Magelang (Central Java). The results show that Bedah Kampung Program began in 2012. The program actually has been around since the 1970s, the last program was called Social Rehabilitation Program, began in 2006. Home improvement terget was 15,000 housing units and enviromental facilities. Until 2011 had been repaired 3,043 houses and 25 environmental facilities. In 2012, already covered 24 regencies/municipalities of 2,140 housing units and 50 environmental facilities. So far, the program has been perceived benefits because it is supported with funds from the state budget, local budget, people who care, and the participation of community in the form of mutual aid and cooperation. The local government’s commitment then began to appear in to support the Ministry of Social Affairs program, although only a few local governments that expressed willingness. Bedah Kampung Program, in addition, still only touch physical aspects not yet that of the economic aspect. Therefore, it is recommended that next program will be continued with productive economic empowerment, improvement of infrastructure and the environment, as well as integration supported by institutional regulations regencies/municipalities and communities.